IDENTIFICATION WORD SPACING OF ERRONEOUS SENTENCES ON INDONESIAN SCIENTIFIC - Ariana, Sunda; Syahputra, Hadi; Kurniawan, Tri Basuki (APTIKOM Journal on Computer Science and Information Technologies, 2020)
Scientific writings in Indonesian language  must the rules of the General Guide to the Reformed Indonesian Spelling especially in terms of word spacing. good word spacing is proportional to the width of the typeface. generally use the align right facility in order to have article look neat in typing, but causes space from word to word over space. Additionally, according to the General Guide book for the updated Indonesian spelling, there are rules that use the distance of words with punctuation after and before punctuation. This research is intended to make for detecting applications using word spacing of the Regular Expression String algorithm and to comment on articles based on principles that are in accordance with the General Guidelines for Indonesian Reformed Spelling.